La biodanza como práctica corporal en relación con la promoción de la salud (2009)
ABSTRACT: The research “Biodance as corporal practice in relation to health promotion” informs of the meaning that people who practice biodance give to the existing relations between corporal practice and health promotion from the point of view of personal aptitude development. The analysis of the results is presented in six chapters: the first recognizes the influence of biodance corporal practice over the health processes; the second shows the relationship between biodance and health; the third explains the relationship between living experiences, creativity, affection, vitality, sexuality, transcendence and health promotion; the fourth shows the existing relationship between music, living experiences and movement; the fifth shows how music, living experiences, and movement allows self-knowledge; and finally, the sixthanalysis describes biodance as a pedagogy to oneself, the others and our environment.